2016
DOI: 10.3892/etm.2016.3128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide on the biological behavior of HepG2 human hepatocellular carcinoma cells

Abstract: Abstract. Many studies have found the function of nitric oxide (NO) in cancer as a pro-neoplastic vs. an anti-neoplastic effector, but the role of NO in hepatocellular carcinoma (HCC) remains unclear. The present study aimed to investigate the effects of nitric oxide (NO) on the biological behavior of the human hepatocellular carcinoma cell line HepG2. HepG2 cell was cultured in vitro and treated with or without sodium nitroprusside (SNP), a NO donor. Subsequently, we evaluated the effects of NO in cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…As a key signaling molecule involved in the regulation of multiple aspects of mitochondrial respiration/oxidative phosphorylation, NO is known to play a vital role in various physiological conditions, and the overproduction of NO is responsible for the pathophysiological development of cancer. The expression of NO depend on a medically relevant dual regulation pathway mediated by traditionally characterized NO synthases (NOS) including inducible (iNOS, NOS2), neuronal (nNOS, NOS1) and endothelial (eNOS, NOS3) types and by enzymatic reduction of available cellular nitrite pools by a diverse class of cytosolic and mitochondrial nitrite reductases ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a key signaling molecule involved in the regulation of multiple aspects of mitochondrial respiration/oxidative phosphorylation, NO is known to play a vital role in various physiological conditions, and the overproduction of NO is responsible for the pathophysiological development of cancer. The expression of NO depend on a medically relevant dual regulation pathway mediated by traditionally characterized NO synthases (NOS) including inducible (iNOS, NOS2), neuronal (nNOS, NOS1) and endothelial (eNOS, NOS3) types and by enzymatic reduction of available cellular nitrite pools by a diverse class of cytosolic and mitochondrial nitrite reductases ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Van de Wouwer et al [14] observed that short- and long-lived NO donors inhibited the proliferation of human neuroblastoma NB69 cells by controlling G1/S transition via transcriptional repressors pRb and cyclin D1 and also by down-regulating systems regulating the S and G2/M phases. Consistent with these results, sodium nitroprusside (SNP), a NO donor, is shown to cause G0/G1 arrest in HepG2 cells [22].…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies reported that nitric oxide inhibited the proliferation of HepG2 cells by blocking cell cycle progression at the G1/S transition [18]. Therefore we performed flow cytometry analysis, with the goal of assessing the effects of the agent on cell cycle.…”
Section: Resultsmentioning
confidence: 99%